Prognostic implications of EBER and EBV DNA combinations in nasopharyngeal carcinoma in endemic areas - Ying Li; Lishui Wu; Zongwei Huang; Sunqiu Cai; Siqi Xu; Jue Wang; Yuxin Yu; Jinghua Lai; Dan Hu; Sufang Qiu (BMC Oral Health)
Abstract Background Epstein-Barr virus-encoded small RNA (EBER) in situ hybridization is the primary biomarker assay employed to infer Epstein-Barr virus (EBV) involvement in nasopharyngeal carcinoma (NPC). However, discordance between EBER status and EBV DNA detection has been observed in certain NPC patients. This study aims to investigate the prognostic significance of EBER and EBV DNA status. Methods A total of 2,942 NPC patients with known EBV status, treated at our center between 2016 and 2022, were included in this analysis. Clinical characteristics and survival outcomes were compared between patients who had EBER-negative versus EBER-positive and who were matched in a 1:4 ratio. The Kaplan-Meier method was used to analyze survival data. The association between EBER-EBV DNA status and survival outcomes was assessed using multivariable analysis. Results Among the cohort, 51 patients (1.7%) were EBER-negative, while 2,891 patients (98.3%) were EBER-positive. EBV-negative NPC was significantly associated with the keratinizing subtype (15.7% vs. 0.3%, P < 0.001). EBER-negative patients exhibited a higher propensity for locoregional recurrence compared to their EBER-positive counterparts, with a 5-year locoregional failure-free survival rate of 76.5% (95% CI, 63.3%-92.5%) versus 86.8% (95% CI, 85.0%-88.6%), respectively (P = 0.012). Multivariable analysis further identified a significant association between double-negative status (EBER-/EBV DNA-) and an increased risk of locoregional recurrence (HR: 4.368, 95% CI, 2.058–9.269, P < 0.001), compared to the double-positive one. These associations remained robust after adjustment for confounding factors and in repeated analyses of the matched cohort. Conclusions This study highlights the potential prognostic value of EBER and EBV DNA combinations in NPC. However, given the limited number of EBV-negative cases, further investigations are warranted to substantiate these findings.